2017
DOI: 10.1002/smll.201701633
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Nanoparticle Clusters Enable Synergistic Integration of Plasmonic and Catalytic Functions in a Single Platform

Abstract: Designing controlled hybrid nanoarchitectures between plasmonic and catalytic materials is of paramount importance to fully exploit each function of constituent materials. This study reports a new synthetic strategy for the realization of colloidal clusters of core-shell nanoparticles with plasmonic cores and catalytically active shells. The Au@M (M = Pd or Pt) nanoparticle clusters (NPCs) with a high density of sub-1 nm interparticle gaps are successfully prepared by the deposition of M shells onto thermally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 53 publications
1
32
0
1
Order By: Relevance
“…Very recently, we demonstrated that the controlled galvanic replacement reaction of Ag NPs with Au precursors could generate robust colloidal Au NP clusters (NPCs) in water, which showed highly enhanced plasmonic performance compared to individual Au NPs owing to their being rich in sub‐1 nm interparticle gaps, namely “hot spots.” Furthermore, the deposition of Pd or Pt shells onto thermally activated Au NPCs could yield stable colloidal clusters of Au@M (M = Pd, Pt) core–shell NPs with precisely controlled topologies . Noticeably, Au@M NPCs exhibited superior plasmon function over their Au@M NP counterparts due to strongly amplified near fields around their interparticle gaps resulting from the plasmonic field coupling between constituent NPs, while the intrinsic catalytic activity of their shells was conserved.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Very recently, we demonstrated that the controlled galvanic replacement reaction of Ag NPs with Au precursors could generate robust colloidal Au NP clusters (NPCs) in water, which showed highly enhanced plasmonic performance compared to individual Au NPs owing to their being rich in sub‐1 nm interparticle gaps, namely “hot spots.” Furthermore, the deposition of Pd or Pt shells onto thermally activated Au NPCs could yield stable colloidal clusters of Au@M (M = Pd, Pt) core–shell NPs with precisely controlled topologies . Noticeably, Au@M NPCs exhibited superior plasmon function over their Au@M NP counterparts due to strongly amplified near fields around their interparticle gaps resulting from the plasmonic field coupling between constituent NPs, while the intrinsic catalytic activity of their shells was conserved.…”
mentioning
confidence: 99%
“…To examine the hydrogen sensing capability of NP assemblies in aqueous solution, the preparation of colloidal NP assemblies with well‐controlled topologies and good suspension stability is critical. In this sense, we prepared Au@Pd core–shell NPCs via the deposition of Pd shells on Au NPCs with enhanced plasmonic performance and remarkable structural stability in aqueous solution by following our previously reported method (see the Supporting Information for synthesis details), and investigated their hydrogen sensing properties in aqueous solution. Au NPCs employed in the production of Au@Pd NPCs consisted of Au NPs with an average size of 34 ± 3 nm (Figure S1a,b, Supporting Information), which were synthesized based on our reported protocol that can enable the generation of stable colloidal Au NPCs with an average interparticle gap size of 0.6 nm .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[21,[25][26][27] In these methods,t he decreased reduction potential of the Au precursors rendered by the AA-induced pre-reduction of Au III to Au I as well as the complex formation between Au precursors and I À ions,the use of PVP and citrate as stabilizers,and the employment of excessive amounts of Au precursors compared to Ag can lead to the formation of NP clusters consisting of several tens of constituent NPs.Wedevised the preparation route to generate the desired Au PIAFs based on these previous findings.I nf act, unlike the previous methods,w hich produced NP clusters,toprepare the Au PIAFs,weconducted the galvanic replacement reactions at 0 8 8Cwithout the use of citrate.T his approach was based on the expectation that the removal of citrate in the growth solution would facilitate the bonding between the initially formed Au nanoparticulate segments,s ince citrate has been demonstrated to protect growing NPs in clusters from agglomeration. [21,[25][26][27] In these methods,t he decreased reduction potential of the Au precursors rendered by the AA-induced pre-reduction of Au III to Au I as well as the complex formation between Au precursors and I À ions,the use of PVP and citrate as stabilizers,and the employment of excessive amounts of Au precursors compared to Ag can lead to the formation of NP clusters consisting of several tens of constituent NPs.Wedevised the preparation route to generate the desired Au PIAFs based on these previous findings.I nf act, unlike the previous methods,w hich produced NP clusters,toprepare the Au PIAFs,weconducted the galvanic replacement reactions at 0 8 8Cwithout the use of citrate.T his approach was based on the expectation that the removal of citrate in the growth solution would facilitate the bonding between the initially formed Au nanoparticulate segments,s ince citrate has been demonstrated to protect growing NPs in clusters from agglomeration.…”
Section: Angewandte Chemiementioning
confidence: 99%